The Effect of an Inclusive School Environment on The Learning Achievement of Children With ADHD In Class III of Primary School - Siti Annnoora Niroha Pulungan; Sunardi Sunardi; Budi Susetyo (Green Publisher Indonesia, 2024)
The background to this research is that ADHD (Attetention Defic Hyperactifity Disorder) children are very dependent on their environment, because they have difficulty focusing and are hyperactive. This will relate to the social and achievement of ADHD children. The aim of this research is to explain the influence of an inclusive school environment on the learning achievement of ADHD children in third grade of elementary school. The method used in this research is descriptive qualitative, which allows researchers to clearly explain social reality through observations and interviews at the research site. A qualitative approach is useful for explaining the influence of an inclusive school environment on the achievement of ADHD children in third grade of elementary school. Qualitative research is an inquiry strategy that plays a role in searching for meaning, understanding, concepts, characteristics, symptoms, symbols and descriptions of an event; focused and multimethod, natural and holistic; prioritizes quality, uses several methods, and is presented narratively. An inclusive school environment has an important role in forming social relationships between students who have obstacles and those who do not have obstacles, so that educational goals can be realized optimally. All school members must be able to carry out their respective obligations, as well as students who have obstacles.